Global trends of cardiovascular disease burden attributable to high body mass index from 1990 to 2021 and projections to 2035 - Huang, Pingping; Guo, Yikun; Ren, Gaocan; Guo, Lijun; Wang, Yifei; Liu, Yicheng; Zhang, Zhibo; Ma, Xiaochang (Frontiers in Cardiovascular Medicine, 2026)
BackgroundCardiovascular disease (CVD) remains the leading cause of mortality and disability globally, with high body mass index (HBMI) playing a pivotal role in its worldwide burden. Gaining a clear understanding and forecasting the effect of HBMI on CVD is crucial for developing effective health policies and interventions.MethodsWe used data from the 2021 Global Burden of Disease study to analyze the CVD burden attributable to HBMI. An age–period–cohort (APC) analysis was conducted to investigate trends in CVD-related mortality attributable to HBMI, whereas the Bayesian Age-Period-Cohort (BAPC) model projected the number of deaths and mortality up to 2035.ResultsThe study revealed a significant increase in CVD deaths and disability-adjusted life years (DALYs) due to HBMI globally, despite slightly decreased age-standardized rates (ASR) for HBMI-related CVD. The ASR of deaths and DALYs decreased from 1990 to 2021 in the high and high-middle Socio-Demographic Index (SDI) regions while increasing in the lower SDI regions. A pinpoint analysis revealed the most significant decline in HBMI-related CVD mortality from 2003 to 2010. The BAPC model projected an increase in global HBMI-related CVD deaths to 2,369,451 by 2035. The ASR of deaths is projected to increase to 37.53 per 100,000, with an increase for females and a decrease for males.ConclusionThis study emphasizes global trends in HBMI-related CVD burden and the importance of targeting HBMI as a modifiable risk factor. It provides crucial information for public health strategies aimed at reducing CVD mortality. Further research is warranted, especially with an aging global population.